Trabajo Decente? Decent Work from a Cuban perspective - Osnaide Izquierdo; Nina Jany (sozialpolitik.ch, 2020)
In this article, we critically examine Cuban social and labour policies as attempts of a practical application of Decent Work principles in a state-socialist context. We start with an examination of past and present models of socio-economic development and labour relations in Cuba. This is followed by an overview of the main Cuban policy principles related to Decent Work, which we contrast with some developments in Cuban labour realities. To contextualize our analysis, we emphasize the conceptualizations of work, production and property, as well as the institutional logics that underly the Cuban labour models and policies. Finally, two policy areas are highlighted by way of example.